Symbolization of Waqf and Ibtida in The Manuscript of The Mushaf al-Quran in The 19 Century: a Study of The Manuscript of Sayyid Ibrahim bin Abdullah al-Jufri - Muhamad Khabib Imdad; Ecep Ismail (Senarai: Journal of Islamic Heritage and Civilization, 2025)
This article examines one of the manuscripts of the al-Qur'an manuscripts stored in the Great Mosque of the Surakarta Palace, namely the copy of Sayyid Ibrahim bin 'Abdullah al-Jufri. The manuscript has many eccentric aspects that are interesting to study further. This article examines the waqf and ibtidā’ symbols that differ from the mushafs that are circulating and read by people in Indonesia. This research employs qualitative with a library research method, namely conducting a literature review by reading, reviewing and analysing various sources. The data collection methods are observation, documentation, interviews and digitalisation. Meanwhile, the data analysis used is a descriptive-analytical method, namely describing data related to the object of study, the results are then analysed critically. Apart from that, this research also uses a philological method, namely the single manuscript edition method. The primary source for this research is Tuan Sayyid Ibrāhīm al- Jufri's manuscript of the Qur'an, while secondary sources are taken from relevant research literature. The study results show that the manuscript of Sayyid Ibrahim al-Jufri's manuscript of the Qur'an applies the symbolisation of waqf and ibtidā’ with five models, namely " تــــ" (waqf tām), " ک" (kāfīy), "ح" (hasan), "الزم" (lazim), and "نبوي " (Nabawiy).